Manufacturing method for carbon molded body and manufacturing method for activated carbon molded body

The method addresses the issue of insufficient strength in carbon molded bodies by using a layered laser sintering process with a specific raw material composition, resulting in high-strength and dense carbon molded bodies.

JP2025054201APending Publication Date: 2025-04-07GUN EI CHEM IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024154133
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2024-09-06
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing methods for manufacturing carbon molded bodies, such as those described in Patent Documents 1 and 2, do not produce carbon molded bodies with sufficient strength.

Method used

A method involving the formation of a thin layer of a raw material mixture containing a molding resin composition and a spherical aggregate, followed by laser irradiation and sintering to create a sintered thin layer. This process is repeated multiple times to form a primary molded body, which is then cured and carbonized to produce a high-strength carbon molded body.

Benefits of technology

The method achieves the production of carbon molded bodies with enhanced strength and density, suitable for complex shapes and applications requiring high rigidity and light weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054201000005
    Figure 2025054201000005
  • Figure 2025054201000006
    Figure 2025054201000006
  • Figure 2025054201000007
    Figure 2025054201000007
Patent Text Reader

Abstract

To provide a manufacturing method for carbon molded bodies and a manufacturing method for activated carbon molded bodies, each of which is capable of manufacturing carbon molded bodies with high strength.SOLUTION: A manufacturing method for carbon molded bodies includes: step (a) of forming a thin layer of a raw material mixture containing a molding resin composition and a spherical aggregate, irradiating a desired region of the thin layer with a laser, and sintering the thin layer to form a sintered thin layer, step (b) of repeating step (a) to obtain a primary molded body in which a plurality of the sintered thin layers are laminated; a step (c) of obtaining a secondary molded body by curing the molding resin composition contained in the primary molded body; and step(d) of obtaining a carbon molded body by carbonizing an organic component contained in the secondary molded body, wherein the molding resin composition contains a phenolic resin and a curing agent, and the ratio of the phenolic resin is 5 pts.mass or more when the total amount of the phenolic resin and the spherical aggregate is 100 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a carbon molded body and a method for producing an activated carbon molded body. [Background technology]

[0002] Carbon materials have excellent properties such as heat resistance, electrical conductivity, thermal conductivity, and chemical stability, and therefore carbon molded articles made of carbon materials are widely used in a wide range of fields, including electrical, electronic, mechanical, metallurgical, and chemical fields. Carbon compacts are obtained by using carbon powder such as coke powder as aggregate and mixing it with a binder such as pitch or tar to form a preform, which is then fired to carbonize it and, if necessary, graphitized. However, in order to obtain a carbon molded body of a desired shape, it is necessary to machine the molded body into the desired shape after carbonization or graphitization, and machining into a complex shape is difficult.

[0003] In view of this, a method for producing a carbon molded body using an additive manufacturing method has been proposed. For example, Patent Document 1 discloses a method for producing a carbon molded body by repeatedly depositing a layer of carbon powder and ink-jetting a binder in desired areas, followed by heating to harden the binder, and carbonizing the resulting hardened product. Patent Document 2 discloses a method for producing a carbon molded body by repeatedly depositing a layer of carbon powder and ink-jetting a binder in desired areas, heating to harden the binder, and impregnating the resulting hardened product with pitch, followed by hardening and carbonization. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2017-535445 [Patent Document 2] Special Publication No. 2018-502811 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the carbon molded bodies obtained by the methods described in Patent Documents 1 and 2 do not have a fully satisfactory strength. An object of the present invention is to provide a method for producing a carbon molded body and a method for producing an activated carbon molded body, which are capable of producing a carbon molded body having high strength. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A method for producing a carbon molded body, comprising the steps of: A step (a) of forming a thin layer of a raw material mixture containing a molding resin composition and a spherical aggregate, irradiating a desired region of the thin layer with a laser, and sintering the thin layer to form a sintered thin layer; A step (b) of performing the step (a) a plurality of times to obtain a primary molded body in which a plurality of the sintered thin layers are laminated; A step (c) of curing the molding resin composition contained in the primary molded body to obtain a secondary molded body; A step (d) of carbonizing the organic components contained in the secondary molded body to obtain a carbon molded body; Including, The molding resin composition contains a phenolic resin and a curing agent, A method for producing a carbon molded body, wherein the proportion of the phenol resin is 5 parts by mass or more when the total of the phenol resin and the spherical aggregate is 100 parts by mass. [2] The method for producing a carbon molded body according to [1] above, wherein the spherical aggregate contains spherical carbon. [3] The method for producing a carbon molded body according to [1] or [2] above, wherein the proportion of the phenolic resin is 5 to 50 parts by mass when the total amount of the phenolic resin and the spherical aggregate is 100 parts by mass. [4] The method for producing a carbon molded body according to any one of [1] to [3] above, further comprising the steps of: (α) impregnating one or more selected from the primary molded body, the secondary molded body, and the carbon molded body with a thermosetting resin; and (β) curing the impregnated thermosetting resin. [5] The method for producing a carbon molded body according to [4] above, further comprising, between the steps (c) and (d), a step (α1) of impregnating the secondary molded body obtained in the step (c) with a thermosetting resin, and a step (β1) of curing the thermosetting resin impregnated in the secondary molded body. [6] The method for producing a carbon molded body according to [4], further comprising, between the step (b) and the step (c), a step (α2) of impregnating the primary molded body obtained in the step (b) with a thermosetting resin. [7] The method for producing a carbon molded body according to [4] above, further comprising, after the step (d), a step (α3) of impregnating the carbon molded body obtained in the step (d) with a thermosetting resin, a step (β3) of curing the thermosetting resin impregnated in the carbon molded body to obtain a tertiary molded body, and a step (γ3) of carbonizing an organic component contained in the tertiary molded body to obtain a carbon molded body. [8] A method for producing an activated carbon molded body, comprising obtaining a carbon molded body by any one of the methods for producing a carbon molded body according to [1] to [7] above, and activating the obtained carbon molded body. Effect of the Invention

[0007] According to the present invention, it is possible to provide a method for producing a carbon molded body and a method for producing an activated carbon molded body, which are capable of producing a carbon molded body with high strength. [Brief description of the drawings]

[0008] [Figure 1] 1 is a graph showing the results of bending strength and density of the secondary molded bodies (I) obtained in Examples 1, 3, 4, 6 and 9. [Diagram 2] 1 is a graph showing the results of bending strength and density of the secondary molded bodies (II) obtained in Examples 3, 4, 6 and 9. [Diagram 3] 1 is a graph showing the results of bending strength and density of the carbon molded bodies (X) obtained in Examples 3, 4, 6 and 9. [Figure 4] 1 is a graph showing the results of bending strength and density of the carbon molded bodies (Y) obtained in Examples 2, 5, 7 and 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following describes in detail the forms for implementing the present invention, but the present invention is not limited to the embodiments described below, and various modifications are possible without departing from the gist of the present invention. In this specification and claims, a numerical range expressed by "to" means a numerical range including the numerical values ​​before and after "to" as the lower and upper limits. For example, A to B is equivalent to A or more and B or less. The numerical ranges of the contents, various physical property values, and property values ​​disclosed in this specification can be arbitrarily combined with the lower and upper limits to form new numerical ranges.

[0010] [Method of manufacturing carbon compacts] "First Aspect" The method for producing a carbon molded article of this embodiment includes the following steps (a) to (d).

[0011] <Process (a)> Step (a) is a step (sintering step) of forming a thin layer of a raw material mixture containing a molding resin composition and spherical aggregates, irradiating a desired area of ​​the thin layer with a laser, and sintering the thin layer to form a sintered thin layer. The molding resin composition is cured by irradiating a desired region of the thin layer with a laser. In this specification, the curing of the molding resin composition in step (a) is also referred to as "primary curing". The raw material mixture used in step (a) contains a molding resin composition and spherical aggregates. In addition to the molding resin composition and the spherical aggregates, the raw material mixture may further contain other components (hereinafter also referred to as "optional components (b)") as necessary, as long as the effects of the present invention are not impaired.

[0012] (Molding resin composition) The molding resin composition contains a phenolic resin and a curing agent. The molding resin composition preferably further contains a curing accelerator. The molding resin composition may further contain components other than the phenolic resin, the curing agent, and the curing accelerator (hereinafter also referred to as "optional component (a)"), if necessary.

[0013] <<Phenol resin>> Examples of the phenolic resin include novolac-type phenolic resins, resol-type phenolic resins, various modified phenolic resins, and mixtures of these. The phenol resin may be used alone or in a mixture of two or more kinds in any ratio.

[0014] Novolac-type phenolic resins are resins obtained by reacting at least one of phenols and bisphenols with aldehydes in the presence of an acid catalyst. Examples of phenols include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 3,5-xylenol, m-ethylphenol, m-propylphenol, m-butylphenol, p-butylphenol, o-butylphenol, resorcinol, hydroquinone, catechol, 3-methoxyphenol, 4-methoxyphenol, 3-methylcatechol, 4-methylcatechol, methylhydroquinone, 2-methylresorcinol, 2,3-dimethylhydroquinone, 2,5-dimethylresorcinol, 2-ethoxyphenol, 4-ethoxyphenol, 4-ethylresorcinol, 3-ethoxy-4-methoxyphenol, 2-propenylphenol, 2-isopropylphenol, 3-isopropylphenol, 4-isopropylphenol, 3,4,5-trimethylphenol, 2-isopropoxyphenol, 4-propoxyphenol, 2-allyl ...propoxyphenol, 4-propoxyphenol, 2-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-propoxyphenol, 4-prop trimethoxyphenol, 4-isopropyl-3-methylphenol, pyrogallol, phloroglucinol, 1,2,4-benzenetriol, 5-isopropyl-3-methylphenol, 4-butoxyphenol, 4-t-butylcatechol, t-butylhydroquinone, 4-t-pentylphenol, 2-t-butyl-5-methylphenol, 2-phenylphenol, 3-phenylphenol, 4-phenylphenol, 3-phenoxyphenol, 4-phenoxyphenol, 4-hexyloxyphenol, 4-hexanoylresorcinol, 3,5-diisopropylcatechol, 4-hexylresorcinol, 4-heptyloxyphenol, 3,5-di-t-butylphenol, 3,5-di-t-butylcatechol, 2,5-di-t-butylhydroquinone, di-sec-butylphenol, 4-cumylphenol, nonylphenol, 2-cyclopentylphenol, 4-cyclopentylphenol, and the like. These phenols may be used alone or in combination of two or more. Examples of bisphenols include bisphenol A, bisphenol F, bisphenol C, bisphenol S, bisphenol E, and bisphenol Z. The bisphenols may be used alone or in combination of two or more kinds in any desired ratio.

[0015] Examples of aldehydes include formaldehyde, trioxane, furfural, paraformaldehyde, benzaldehyde, methyl hemiformal, ethyl hemiformal, propyl hemiformal, salicylaldehyde, butyl hemiformal, phenyl hemiformal, acetaldehyde, propyl aldehyde, phenylacetaldehyde, α-phenylpropyl aldehyde, β-phenylpropyl aldehyde, o-hydroxybenzaldehyde, m-hydroxybenzaldehyde, p-hydroxybenzaldehyde, o-chlorobenzaldehyde, o-nitrobenzaldehyde, m-nitrobenzaldehyde, p-nitrobenzaldehyde, o-methylbenzaldehyde, m-methylbenzaldehyde, p-methylbenzaldehyde, p-ethylbenzaldehyde, and pn-butylbenzaldehyde. The aldehydes may be used alone or in a mixture of two or more kinds in any ratio.

[0016] Examples of the acid catalyst include hydrochloric acid, sulfuric acid, phosphoric acid, sulfonic acid, carboxylic acid, and salts with metals such as zinc chloride or zinc acetate. Examples of sulfonic acids include paratoluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, and methanesulfonic acid. Examples of the carboxylic acid include lactic acid, citric acid, malic acid, tartaric acid, malonic acid, succinic acid, maleic acid, oxalic acid, acetic acid, and benzoic acid. The acid catalyst may be used alone or in combination of two or more kinds in any desired ratio.

[0017] The reaction of at least one of phenols and bisphenols with aldehydes can be carried out by a known method. For example, a method of charging at least one of phenols and bisphenols, aldehydes, an acid catalyst, water, etc. into a reaction vessel and maintaining an arbitrary reaction temperature for an arbitrary reaction time can be mentioned. After the reaction is completed, the reaction liquid is neutralized as necessary, and the reaction liquid is further concentrated under reduced pressure to remove water, thereby obtaining a novolac type phenolic resin. In addition, a silane coupling agent may be added as necessary before or after neutralization of the reaction liquid. In this case, a mixture containing a novolac type phenolic resin and a silane coupling agent is obtained. Examples of the silane coupling agent include N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane. The silane coupling agent may be used alone or in combination of two or more kinds in any desired ratio.

[0018] The mass average molecular weight of the novolac phenolic resin is preferably 2000 to 20000, more preferably 3000 to 17000, and even more preferably 4000 to 15000. If the mass average molecular weight of the novolac phenolic resin is equal to or greater than the lower limit, the raw material mixture is less likely to block. As will be described in detail later, the primary molded body obtained in step (b) is removed by removing the raw material mixture from the region (non-irradiated region) where the thin layer of laser is not irradiated. The less the raw material mixture is blocked, the easier it is to remove the raw material mixture from the non-irradiated region, and the time required to remove the primary molded body (removal work time) can be shortened, improving the workability of removal. If the mass average molecular weight of the novolac phenolic resin is equal to or less than the upper limit, the novolac phenolic resin can be easily produced. The mass average molecular weight of the novolac phenolic resin is a value measured by gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0019] The average particle size of the novolac phenolic resin is preferably 5 to 100 μm, more preferably 10 to 80 μm. If the average particle size of the novolac phenolic resin is equal to or greater than the lower limit, the flowability of the raw material mixture is increased, and the recoatability is excellent. If the average particle size of the novolac phenolic resin is equal to or less than the upper limit, the thin layer of the raw material mixture can be easily thinned, the laser is sufficiently irradiated to the inside of the thin layer, and the molding resin composition is sufficiently cured. In addition, the smoothness of the surface of the sintered thin layer during laser irradiation is improved. The average particle size of the novolac phenolic resin is a particle size (median size) corresponding to a cumulative frequency of 50% based on the volume distribution of the novolac phenolic resin measured by a laser diffraction method.

[0020] The resol type phenolic resin is a resin obtained by reacting at least one of a phenol and a bisphenol with an aldehyde in the presence of a basic catalyst. Examples of the phenols and aldehydes include the phenols and aldehydes exemplified above in the description of the novolac type phenolic resin. Examples of the basic catalyst include hydroxides of alkali metals such as sodium hydroxide and lithium hydroxide, hydroxides of alkaline earth metals such as calcium hydroxide and barium hydroxide, ammonium hydroxide, amines such as diethylamine, triethylamine, triethanolamine, ethylenediamine, hexamethylenetetramine, etc. These basic catalysts may be used alone or in combination of two or more in any ratio.

[0021] The resol type phenolic resin is usually obtained in a state of being dispersed in a solvent such as water (hereinafter, the resol type phenolic resin in this state will be referred to as "liquid resol type phenolic resin"). The resol type phenolic resin may be used in a liquid state, or the liquid resol type phenolic resin may be subjected to a dehydration treatment or the like to remove the solvent, and then dried at room temperature to be used in a solid state. In addition, in order to improve strength, a silane coupling agent may be added to the resol type phenolic resin during the manufacturing process. If a silane coupling agent is not added during the manufacturing process, the resol type phenolic resin may be used in combination with a silane coupling agent. Examples of the silane coupling agent include the silane coupling agents exemplified above in the explanation of the novolac type phenolic resin.

[0022] Examples of various modified phenolic resins include novolac-type phenolic resins or resol-type phenolic resins modified by known techniques such as boron modification, silicon modification, heavy metal modification, nitrogen modification, sulfur modification, oil modification, and rosin modification.

[0023] The phenol resin may be used alone or in a mixture of two or more kinds in any ratio. Among the above, as the phenolic resin, novolac type phenolic resin and resol type phenolic resin are preferred, and from the viewpoint that the powder can be easily laminated when the phenolic resin is in a solid form, novolac type phenolic resin and solid resol type phenolic resin are more preferred, and novolac type phenolic resin is particularly preferred. Novolac-type phenolic resins have better thermal stability than resol-type phenolic resins, and are less likely to undergo unintended polymerization when heated during melting. This allows them to be stably molded into various shapes.

[0024] <<Hardening agent>> Examples of the hardener include hexamethylenetetramine, hexaethylenetetramine, hexamethoxymethylolmelamine, etc. Among these, hexaethylenetetramine is preferred from the viewpoints of storage stability and cost. The curing agent may be used alone or in combination of two or more kinds in any desired ratio.

[0025] <<Curing accelerator>> Examples of the hardening accelerator include benzoic acid, salicylic acid, and resorcinol. The curing accelerator may be used alone or in combination of two or more kinds in any desired ratio.

[0026] <<Optional component (a)>> Optional ingredients include, for example, flow aids, boron carbide, silane coupling agents, and the like.

[0027] (spherical aggregate) Spherical aggregate is a particulate material. The sphericity of the spherical aggregate is preferably 0.7 to 1.0, more preferably 0.8 to 1.0, and even more preferably 0.95 to 1.0. If the sphericity of the spherical aggregate is within the above range, the strength variation from one part to another in the carbon molded body is reduced. In particular, if the sphericity of the spherical aggregate is equal to or greater than the above lower limit, the raw material mixture can be spread uniformly when forming a thin layer. The sphericity of spherical aggregate is an index determined by (diameter of a circle equal to the projected area of ​​the particle) / (diameter of the smallest circle circumscribing the projected image of the particle). The closer this index is to 1.0, the closer the particle is to a perfect sphere.

[0028] The average particle size of the spherical aggregate is preferably 10 to 150 μm, more preferably 20 to 80 μm, and even more preferably 40 to 60 μm. If the average particle size of the spherical aggregate is equal to or greater than the lower limit, the raw material mixture can be spread evenly when forming a thin layer. If the average particle size of the spherical aggregate is equal to or less than the upper limit, even carbon molded bodies having complex and fine shapes can be easily manufactured. The average particle size of the spherical aggregate is the particle size (median size) corresponding to a cumulative frequency of 50% based on the volume distribution of the spherical aggregate measured by a laser diffraction method.

[0029] Examples of the spherical aggregate include spherical thermosetting resin cured products and spherical carbon. As the spherical thermosetting resin cured product, for example, a spherical cured product of phenol resin can be used. The spherical cured product of phenol resin can be obtained by condensation reaction of phenols and aldehydes in an aqueous medium in the presence of a condensation reaction catalyst and an emulsifying dispersant under high temperature and high pressure conditions. Specifically, a fully cured spherical phenol resin can be mentioned, and more specifically, the HF series manufactured by Gun-ei Chemical Industry Co., Ltd. is preferable. The spherical carbon can be obtained, for example, by carbonizing the above-mentioned spherical thermosetting resin cured product in a nitrogen atmosphere at a temperature of 400 to 1000° C. Specifically, the GC series manufactured by Gun-ei Chemical Industry Co., Ltd. is preferred.

[0030] The spherical aggregate may be used alone or in combination of two or more kinds in any ratio. Among the above, spherical carbon is preferred as the spherical aggregate.

[0031] The spherical aggregate may be surface-treated with a coupling agent or the like. By subjecting the spherical aggregate to a surface treatment, the adhesiveness between the spherical aggregate and the molding resin composition can be improved. Examples of such coupling agents include silane coupling agents, titanate coupling agents, and aluminum coupling agents. Examples of the silane coupling agent include γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-aminopropyltriethoxysilane, N,N-bis[3-(trimethoxysilyl)propyl]amine, N,N-bis[3-(trimethoxysilyl)propyl]ethylenediamine, N,N-bis[3-(trimethoxysilyl)propyl]methacrylamide, N-glycidyl-N,N-bis[3-(trimethoxysilyl)propyl]amine, γ-aminopropyltetraethoxydisiloxane, N,N-bis[3-(methyldimethoxysilyl)propyl]amine, N,N-bis[3-(methyldimethoxysilyl)propyl]ethylenediamine, N,N-bis[3-(methyldimethoxysilyl)propyl]methacrylamide, and N-glycidyl-N,N-bis[3-(methyldimethoxysilyl)propyl]amine. Examples of titanate coupling agents include isopropyl triisostearoyl titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, and bis(dioctyl pyrophosphate)ethylene titanate. Examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum alkyl acetoacetate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), diisopropoxyaluminum monomethacrylate, aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer. The coupling agent may be used alone or in combination of two or more kinds in any desired ratio.

[0032] (Optional component (b)) Examples of the optional component (b) include graphite, glassy carbon, carbon fiber, carbon black, graphene, fullerene, carbon nanotube, carbon nanohorn, acetylene black, and ketjen black. The optional component (b) may be used alone or as a mixture of two or more kinds in any ratio.

[0033] (Content) The proportion of the phenolic resin is 5 parts by mass or more, preferably 5 to 50 parts by mass, more preferably 15 to 40 parts by mass, and even more preferably 20 to 30 parts by mass, when the total of the phenolic resin and the spherical aggregate is 100 parts by mass. If the proportion of the phenolic resin is equal to or more than the lower limit, a carbon molded body having sufficient strength and density can be obtained. If the proportion of the phenolic resin is equal to or less than the upper limit, the portion irradiated with the laser is easily sintered (primary curing), and the surface smoothness of the sintered thin layer is improved. Therefore, the next thin layer can be laid evenly on the sintered thin layer, and the primary molded body is less likely to become brittle. If the proportion of the phenolic resin exceeds the upper limit, the phenolic resin in the portion irradiated with the laser may aggregate, forming a sintered thin layer with a sea-island structure. The sintered thin layer with a sea-island structure has poor surface smoothness, making it difficult to lay the next thin layer evenly, and the primary molded body may become brittle.

[0034] The ratio of the spherical aggregate is 95 parts by mass or less, preferably 50 to 95 parts by mass, more preferably 60 to 85 parts by mass, and even more preferably 70 to 80 parts by mass, when the total of the phenolic resin and the spherical aggregate is 100 parts by mass. If the ratio of the spherical aggregate is equal to or more than the lower limit, the portion irradiated with the laser is easily sintered uniformly (primary hardening), and the smoothness of the surface of the sintered thin layer is improved. Therefore, the next thin layer can be laid uniformly on the sintered thin layer, and the primary molded body is less likely to become brittle. If the ratio of the spherical aggregate is equal to or less than the upper limit, a carbon molded body with sufficient strength and density can be obtained.

[0035] The ratio of the curing agent is preferably 3 to 25 parts by mass, more preferably 5 to 20 parts by mass, and even more preferably 7 to 18 parts by mass, relative to 100 parts by mass of the phenolic resin. If the ratio of the curing agent is equal to or higher than the lower limit, the phenolic resin is sufficiently cured. If the ratio of the curing agent is equal to or lower than the upper limit, the generation of gases such as ammonia can be reduced.

[0036] The ratio of the curing accelerator is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4.5 parts by mass, and even more preferably 1.5 to 4.5 parts by mass, relative to 100 parts by mass of the phenolic resin. If the ratio of the curing accelerator is equal to or greater than the lower limit, the curing of the phenolic resin is accelerated, and the gelling time of the molding resin composition is shortened. If the ratio of the curing accelerator is equal to or less than the upper limit, a decrease in strength due to excessive addition can be suppressed.

[0037] (Preparation of raw material mixture) The raw material mixture is obtained by mixing a molding resin composition with spherical aggregates.

[0038] (Formation of thin sintered layer) The formation of the sintered thin layer will be described later in step (b).

[0039] <Process (b)> The step (b) is a step (lamination step) in which the step (a) is carried out a plurality of times to obtain a primary molded body in which a plurality of the sintered thin layers are laminated. The above-mentioned steps (a) and (b) are carried out, for example, by three-dimensional additive manufacturing as follows. As the three-dimensional additive manufacturing, a selective laser sintering method (SLS method) is suitable.

[0040] First, three-dimensional data of the cross-sectional shape of the desired carbon molded body at a fixed interval is created in advance. Based on this three-dimensional data, a thin layer made of a raw material mixture is laminated on the bottom surface of a molding chamber installed in a three-dimensional lamination device such as a powder additive manufacturing machine. A laser is scanned and irradiated to heat the desired area of ​​this thin layer, thereby sintering the thin layer to form a sintered thin layer (step (a)). The bottom of the modeling chamber is a modeling table, which can be moved up and down. After the sintered thin layer is formed, the bottom surface of the building chamber (the building table) is lowered by one layer, another thin layer of the raw material mixture is laminated on the sintered thin layer, and the desired area of ​​this thin layer is scanned and irradiated with a laser. These lamination and irradiation operations are repeated until the desired carbon molded body is formed, and a primary molded body is obtained (step (b)). The thickness of one thin layer is preferably 30 to 200 μm, and more preferably 50 to 150 μm.

[0041] It is preferable to use a laser with an irradiation output (laser intensity) of 10 W or more. This melts the molding resin composition contained in the raw material mixture, and the raw material mixture is sintered stably (primary curing). The laser intensity is preferably 10 to 100 W, and more preferably 30 to 60 W. Types of lasers include CO2 lasers, YAG lasers, and semiconductor lasers.

[0042] The laser diameter (spot diameter) is preferably 0.05 to 1.5 mm, more preferably 0.05 to 1.4 mm, even more preferably 0.1 to 1.0 mm, particularly preferably 0.15 to 0.5 mm, and most preferably 0.18 to 0.4 mm. If the laser diameter is equal to or greater than the lower limit, the primary molded body can be produced in a short time. If the laser diameter is equal to or less than the upper limit, even a carbon molded body having a complex and fine shape can be easily produced. The laser diameter is the diameter of the laser when it hits the thin layer.

[0043] The laser scanning speed is preferably 1 to 20 m / sec, more preferably 3 to 15 m / sec, and even more preferably 5 to 15 m / sec. If the laser scanning speed is equal to or higher than the lower limit, the primary molded body can be produced in a short time. In addition, molding defects are unlikely to occur, and even carbon molded bodies having complex and fine shapes can be easily produced. In addition, smoke and gas are unlikely to be generated, and the equipment is unlikely to be worn out. If the laser scanning speed is equal to or lower than the upper limit, a carbon molded body having higher strength can be easily obtained.

[0044] The laser scanning interval is preferably 0.005 to 0.6 mm, more preferably 0.01 to 0.5 mm, and even more preferably 0.1 to 0.2 mm. If the laser scanning interval is equal to or greater than the above lower limit, the primary molded body can be produced in a short time. In addition, molding defects are unlikely to occur, and even carbon molded bodies having complex and fine shapes can be easily produced. In addition, smoke and gas are unlikely to be generated, and the device is unlikely to wear out. If the laser scanning interval is equal to or less than the above upper limit, a carbon molded body having higher strength can be easily obtained.

[0045] <Process (c)> Step (c) is a step (curing step) of curing the molding resin composition contained in the primary molded body to obtain a secondary molded body. In this specification, the curing of the molding resin composition in step (c) is also referred to as "secondary curing".

[0046] The primary molded body is shaped while being embedded in the powder of the raw material mixture. Therefore, prior to the secondary curing of the molding resin composition, the raw material mixture in the area (non-irradiated area) where the thin layer of laser is not irradiated, i.e., the raw material mixture where the molding resin composition is not primarily cured, is removed with a brush or a vacuum cleaner, etc., to remove the primary molded body. Then, the removed primary molded body is moved to, for example, a thermostatic oven and heat-treated to secondary cure the molding resin composition. The molding resin composition in the area irradiated with the thin laser has undergone primary curing and has an appropriate strength, so that the primary molded body is less likely to collapse when the raw material mixture in the non-irradiated area of ​​the thin layer is removed to take out the primary molded body, and the primary molded body can be easily taken out and moved.

[0047] The curing temperature and curing time of the secondary curing may be appropriately adjusted in consideration of the size, shape, etc. of the carbon molded body to be obtained. Usually, the curing temperature is about 130 to 300° C., and preferably 150 to 250° C. The curing time is about 1 to 120 minutes, preferably 10 to 90 minutes, and more preferably 30 to 60 minutes. The secondary curing may be carried out under normal pressure or under pressure.

[0048] <Process (d)> Step (d) is a step (carbonization step) of obtaining a carbon molded body by carbonizing the organic components contained in the secondary molded body. The organic components contained in the secondary molded body are those derived from organic compounds in the molding resin composition contained in the raw material mixture, specifically, cured products of phenolic resins, uncured phenolic resins, curing agents, curing accelerators, etc. In addition, when a spherical cured thermosetting resin is used as the spherical aggregate, the spherical cured thermosetting resin is also included in the organic components. The carbonization treatment for carbonizing the secondary molded body may be carried out under normal pressure or under reduced pressure (vacuum). The carbonization treatment may be carried out under an oxidizing atmosphere or an inert atmosphere. In particular, the carbonization treatment is preferably carried out under reduced pressure and an inert atmosphere. Here, the "oxidizing atmosphere" refers to an air atmosphere or an atmosphere containing a known oxidizing substance such as oxygen. To provide an inert atmosphere, an inert gas such as helium, argon, or nitrogen may be used.

[0049] The carbonization temperature and time of the carbonization treatment may be appropriately adjusted in consideration of the type of phenolic resin contained in the raw material mixture, the size and shape of the carbon molded body to be obtained, etc. In general, the carbonization temperature is preferably 300 to 1200° C., and more preferably 500 to 1000° C. The carbonization time is preferably 10 minutes to 25 hours, more preferably 30 minutes to 10 hours, and even more preferably 30 minutes to 5 hours.

[0050] The steps (c) and (d) may be carried out in separate apparatuses, or may be carried out in the same apparatus as long as the temperature can be adjusted to the desired level. When steps (c) and (d) are carried out in separate devices, after step (c), the secondary molded body is cooled to a temperature at which it can be removed from the device such as an incubator, and then moved to another device such as an incubator or a carbonization furnace and subjected to step (d). When steps (c) and (d) are carried out in the same equipment, an incubator or other such equipment is set to a desired temperature and the primary molded body is heat-treated to form a secondary molded body (step (c)), and then the temperature of the same equipment is raised to the desired temperature and the secondary molded body is further heat-treated to obtain a carbon molded body (step (d)). If necessary, the carbon compact may be graphitized after step (d) by, for example, heating the carbon compact in an inert atmosphere at a maximum temperature of more than 1200° C. but not exceeding 3000° C. to obtain a graphitized carbon compact.

[0051] <Action and effect> According to the method for producing a carbon molded body of the present embodiment described above, a raw material mixture containing a specific amount of phenolic resin is used to form a primary molded body by primary curing of a molding resin composition by three-dimensional additive manufacturing. Therefore, since the amount of resin per layer in the laser irradiation area is greater than when a binder is ink-jetted, the amount of carbon contained in the carbon molded body is sufficient, and a carbon molded body with high strength can be obtained. In addition, since the molding resin composition is primarily cured, the primary molded body has a suitable strength even before step (c). Therefore, the primary molded body can be easily removed from the non-irradiated area and is easy to handle. In addition, since the non-irradiated area is removed at the step (c), the device such as an incubator used for secondary curing can be made smaller. Moreover, since the molding resin composition is sufficiently cured in the primary molded body, the secondary molded body is less likely to warp or shrink compared to the primary molded body, even if the primary molded body is subjected to a secondary curing treatment.

[0052] <Application> The carbon molded article obtained by the present invention is suitable as a component requiring light weight, high strength, and high rigidity, and is widely used, for example, in various parts of aircraft, automobiles, ships, and other types of transportation equipment, semiconductor manufacturing equipment, medical equipment, batteries, sporting goods, leisure goods, etc.

[0053] <Other forms> It is preferable that the method for producing a carbon molded body of this embodiment further includes a step (α) of impregnating one or more selected from the primary molded body obtained in step (b), the secondary molded body obtained in step (c), and the carbon molded body obtained in step (d) with a thermosetting resin, and a step (β) of curing the impregnated thermosetting resin. By impregnating the carbon molded article with a thermosetting resin, the thermosetting resin penetrates into the gaps between the spherical aggregates and the cured product of the molding resin composition, increasing the amount of resin, and thus a carbon molded article with higher strength can be obtained. In the step (α), a curing agent or a curing accelerator may be used in addition to the thermosetting resin. In the present invention, the thermosetting resin with which one or more selected from the primary molded body, the secondary molded body, and the carbon molded body are impregnated is also referred to as "impregnating resin".

[0054] Examples of the thermosetting resin include phenol resin, epoxy resin, furan resin, melamine resin, unsaturated polyester resin, polyurethane resin, polyimide resin, and pitch. The phenol resin may be the phenol resin exemplified in step (a) of the first embodiment.

[0055] Examples of epoxy resins include phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, biphenol type epoxy resins, naphthalene type epoxy resins, anthracene type epoxy resins, naphthol type epoxy resins, xylylene type epoxy resins, biphenyl aralkyl type epoxy resins, triphenylmethane type epoxy resins, dicyclopentadiene type epoxy resins, stilbene type epoxy resins, sulfur atom-containing epoxy resins, and phosphorus atom-containing epoxy resins.

[0056] Furan resin is a resin whose main raw materials are furfuryl alcohol, urea, formaldehyde, etc., and hardens through polycondensation while undergoing a dehydration reaction in the presence of an acid catalyst. The furan resin to be used preferably contains, as a main component, one or more condensates or co-condensates of either furfuryl alcohol or furfuryl alcohol and urea with aldehydes, and a mixture with furfuryl alcohol, and optionally contains at least one of a phenol and a bisphenol. Examples of the phenols and aldehydes include the phenols and aldehydes exemplified above in the description of the phenolic resin of the first embodiment.

[0057] In addition, a furfuryl alcohol condensate obtained by subjecting furfuryl alcohol alone to a condensation reaction in the presence of an acid catalyst may be used as the furan resin. Examples of the acid catalyst include the acid catalysts exemplified in step (a) of the first embodiment. In particular, carboxylic acids are preferred, and citric acid is more preferred.

[0058] The thermosetting resin may be used alone or in combination of two or more kinds in any desired ratio. Among the above, from the viewpoint of easily achieving a high carbon residue rate, the thermosetting resin is preferably a phenol resin, an epoxy resin, a furan resin, or pitch, more preferably a phenol resin, and even more preferably a resol-type phenol resin.

[0059] The thermosetting resin may be liquid or solid at, for example, 25°C. If it is solid, it is preferable to dissolve or disperse it in a solvent and impregnate one or more selected from the primary molded body, secondary molded body, and carbon molded body with the resin in a liquid state, i.e., in the form of a resin solution. Examples of the solvent include water, methanol, and acetone. The solvent may be used alone or in combination of two or more kinds in any ratio.

[0060] The ratio of the thermosetting resin to the total mass of the resin solution is preferably 30 to 99 mass%, more preferably 45 to 99 mass%, and even more preferably 60 to 99 mass%, calculated as a pure content. If the ratio of the thermosetting resin is equal to or more than the lower limit, the strength of the carbon molded body is further increased.

[0061] The viscosity of the resin solution at 25° C. is preferably 10 to 1000 mPa s, more preferably 10 to 500 mPa s, and even more preferably 10 to 100 mPa s. When the viscosity of the resin solution is equal to or less than the above upper limit, the impregnation property of the resin solution is improved, and a carbon molded body having higher strength can be easily obtained. The viscosity of the resin solution is a value measured at 25°C using a Brookfield viscometer.

[0062] When the thermosetting resin is liquid at 25°C, it may be directly impregnated into one or more selected from the primary molded body, the secondary molded body, and the carbon molded body, or may be diluted with a solvent as necessary until the desired concentration or viscosity is achieved. Examples of the solvent include the solvents exemplified above in the explanation of the resin solution.

[0063] Step (α) may be carried out between step (b) and step (c), between step (c) and step (d), or after step (d). In the present invention, step (α) performed between step (c) and step (d) is particularly referred to as "step (α1)", step (α) performed between step (b) and step (c) is particularly referred to as "step (α2)", and step (α) performed after step (d) is particularly referred to as "step (α3)". In addition, step (β) performed after step (α1) is particularly referred to as "step (β1)", step (β) performed after step (α2) is particularly referred to as "step (β2)", and step (β) performed after step (α3) is particularly referred to as "step (β3)".

[0064] The method for producing a carbon molded body preferably includes one or more of steps (α1), (α2), and (α3). That is, the method for producing a carbon molded body may include one of steps (α1), (α2), and (α3), or may include a combination of two or more of steps (α1), (α2), and (α3). Furthermore, each of the step (α1), the step (α2) and the step (α3) may be carried out once or two or more times. When the method for producing a carbon molded body includes the step (α3), it further includes a step (γ3) which is a carbonization step described below, after the step (β3). Hereinafter, one embodiment of the method for producing a carbon molded body including the steps (α) and (β) will be described.

[0065] "Second Aspect" The method for producing a carbon molded body of this embodiment includes steps (a) to (d) described in the first aspect, and further includes steps (α1) and (β1) described below between steps (c) and (d). Incidentally, since steps (a) to (d) are the same as those in the first embodiment, the explanation thereof will be omitted.

[0066] <Process (α1)> Step (α1) is step (α) carried out between step (c) and step (d), and specifically, is a step (impregnation step) of impregnating the secondary molded body obtained in step (c) with a thermosetting resin. By impregnating the secondary molded body with a thermosetting resin, the thermosetting resin penetrates into the gaps between the spherical aggregates and the cured product of the molding resin composition, increasing the amount of resin, resulting in a carbon molded body with greater strength.

[0067] The method for impregnating the secondary molded body with the thermosetting resin is not particularly limited, but examples thereof include a method in which the secondary molded body is immersed in the thermosetting resin (dipping method), a method in which the thermosetting resin is applied to the secondary molded body by flow coating (spraying) method, spraying method, brush coating method, etc. The amount of thermosetting resin to be impregnated is not particularly limited, but it is preferable to impregnate, for example, 5 parts by mass or more of thermosetting resin in terms of pure content with respect to 100 parts by mass of the secondary molded body before impregnation. The step (α1) may be performed once or twice or more.

[0068] <Process (β1)> The step (β1) is a step (β) carried out after the step (α1), and specifically, is a step (curing step) of curing the thermosetting resin impregnated into the secondary molded body. In this specification, the curing of the thermosetting resin in step (β1) is also referred to as "tertiary curing".

[0069] The curing temperature and curing time of the tertiary curing may be appropriately adjusted in consideration of the size, shape, etc. of the secondary molded body. Usually, the curing temperature is about 130 to 300° C., and preferably 150 to 250° C. The curing time is about 1 to 120 minutes, preferably 10 to 90 minutes, and more preferably 30 to 60 minutes. The tertiary curing may be carried out under normal pressure or under pressure. When the step (α1) is carried out two or more times, the step (β1) may be carried out once after the step (α1) is carried out two or more times, or the step (α1) and the step (β1) may be carried out alternately and repeatedly.

[0070] In this specification, the secondary molded product provided in step (α1) is also referred to as "secondary molded product (I)", and the secondary molded product obtained after curing the thermosetting resin impregnated in the secondary molded product (I) (however, when step (β1) is performed twice or more, the secondary molded product obtained in the last step (β1)), i.e., the secondary molded product provided in step (d), is also referred to as "secondary molded product (II)". The secondary molded product (II) is a cured product obtained by curing the molding resin composition and the thermosetting resin. In step (d), the organic components contained in the secondary molded body (II) are carbonized. In this embodiment, the organic components contained in the secondary molded body (II) are those derived from organic compounds in the molding resin composition contained in the raw material mixture, specifically, the cured product of the phenolic resin, the uncured phenolic resin, the curing agent, the curing accelerator, and the cured product of the thermosetting resin. In addition, when a spherical thermosetting resin cured product is used as the spherical aggregate, the spherical thermosetting resin cured product is also included in the organic components.

[0071] "Third Aspect" The method for producing a carbon molded body of this embodiment includes steps (a) to (d) described in the first aspect, and further includes the following step (α2) between steps (b) and (c). Incidentally, since steps (a) to (d) are the same as those in the first embodiment, the explanation thereof will be omitted.

[0072] <Process (α2)> Step (α2) is step (α) carried out between step (b) and step (c), and is specifically a step (impregnation step) of impregnating the primary molded body obtained in step (b) with a thermosetting resin. By impregnating the primary molded body with a thermosetting resin, the thermosetting resin penetrates into the gaps between the spherical aggregates and the molding resin composition, increasing the amount of resin, thereby obtaining a carbon molded body with higher strength.

[0073] The method of impregnating the primary molded body with the thermosetting resin and the amount of the thermosetting resin to be impregnated are the same as those exemplified in the step (α1) of the second embodiment. The step (α2) may be performed once or twice or more.

[0074] In this specification, the primary molded body to be subjected to step (α2) is also referred to as the "primary molded body (I)", and the primary molded body obtained after impregnating the primary molded body (I) with a thermosetting resin (however, in the case where step (α2) is performed two or more times, the primary molded body obtained in the final step (α2)), i.e., the primary molded body to be subjected to step (c), is also referred to as the "primary molded body (II)". In step (c), the molding resin composition contained in the primary molded body (II) is further cured, and at this time, the thermosetting resin contained in the primary molded body (II) is also cured. That is, the secondary molded body obtained in step (c) of this embodiment is a cured product in which the molding resin composition and the thermosetting resin are cured. In the third aspect, step (c) also serves as step (β) performed after step (α2), that is, step (β2). When step (α2) is performed two or more times, step (c) may be performed once after step (α2) is performed two or more times, or step (α2) and step (c) may be performed alternately and repeatedly. In step (d), the organic components contained in the secondary molded body are carbonized. In this embodiment, the organic components contained in the secondary molded body are the same as those in the second embodiment, that is, the cured product of the phenolic resin, the uncured phenolic resin, the curing agent, the curing accelerator, and the cured product of the thermosetting resin. In addition, when a spherical thermosetting resin cured product is used as the spherical aggregate, the spherical thermosetting resin cured product is also included in the organic components.

[0075] The method for producing a carbon molded body according to the present embodiment may further include steps (α1) and (β1) between steps (c) and (d) as necessary. Steps (α1) and (β1) are the same as those in the second embodiment.

[0076] "Fourth Aspect" The method for producing a carbon molded body of this embodiment includes steps (a) to (d) described in the first aspect, and further includes, after step (d), the steps (α3), (β3) and (γ3) described below. Incidentally, since steps (a) to (d) are the same as those in the first embodiment, the explanation thereof will be omitted.

[0077] <Process (α3)> The step (α3) is a step (α) carried out after the step (d), and specifically, is a step (impregnation step) of impregnating the carbon molded body obtained in the step (d) with a thermosetting resin. By impregnating the carbon molding with a thermosetting resin, the thermosetting resin penetrates into the gaps between the spherical aggregate and the carbonized material of the molding resin composition, increasing the amount of resin, thereby obtaining a carbon molding with greater strength. In the step (α3), the graphitized carbon body may be impregnated with a thermosetting resin.

[0078] The method of impregnating the carbon molded body with the thermosetting resin and the amount of the thermosetting resin to be impregnated are the same as those exemplified in step (α1) of the second embodiment. The step (α3) may be performed once or twice or more.

[0079] In this specification, the carbon molded body subjected to step (α3) is also referred to as "carbon molded body (I)," and the carbon molded body obtained in the step (γ3) described below (however, in the case where step (γ3) is performed twice or more, the final step (γ3)) is also referred to as "carbon molded body (II)."

[0080] <Process (β3)> Step (β3) is step (β) carried out after step (α3), and specifically, is a step (curing step) of curing the thermosetting resin impregnated into the carbon molding (I) to obtain a tertiary molding. In this specification, the curing of the thermosetting resin in step (β3) is also referred to as “tertiary curing.” When the method for producing a carbon molded body of this embodiment includes step (β1), the curing of the thermosetting resin in step (β1) is also referred to as “tertiary curing,” and the curing of the thermosetting resin in step (β3) is also referred to as “quaternary curing.”

[0081] The curing temperature and curing time of the tertiary curing may be appropriately adjusted in consideration of the size, shape, etc. of the carbon molded body (I). Usually, the curing temperature is about 130 to 300° C., and preferably 150 to 250° C., and the curing time is about 1 to 120 minutes, and preferably 10 to 90 minutes, and more preferably 30 to 60 minutes. The tertiary curing may be carried out under normal pressure or under pressure. When the step (α3) is performed two or more times, the step (β3) may be performed once after the step (α3) is performed two or more times, or the step (α3) and the step (β3) may be performed alternately and repeatedly.

[0082] <Process (γ3)> The step (γ3) is a step carried out after the step (β3), and is a step (carbonization step) for obtaining a carbon body (II) by carbonizing the organic components contained in the tertiary molded body. In this specification, the carbonization of the organic components in step (d) is also referred to as "primary carbonization", and the carbonization of the organic components in step (γ3) is also referred to as "secondary carbonization".

[0083] The organic component contained in the tertiary molded body is a cured product of a thermosetting resin. The carbonization treatment for carbonizing the tertiary molded body may be carried out under normal pressure or under reduced pressure (vacuum). The carbonization treatment may be carried out under an oxidizing atmosphere or an inert atmosphere. In particular, the carbonization treatment is preferably carried out under reduced pressure and an inert atmosphere. Here, the "oxidizing atmosphere" refers to an air atmosphere or an atmosphere containing a known oxidizing substance such as oxygen. To provide an inert atmosphere, an inert gas such as helium, argon, or nitrogen may be used.

[0084] The carbonization temperature and time of the carbonization treatment may be appropriately adjusted in consideration of the type of thermosetting resin, the size and shape of the carbon molded body, etc. In general, the carbonization temperature is preferably 300 to 1200° C., and more preferably 500 to 1000° C. The carbonization time is preferably 10 minutes to 25 hours, more preferably 30 minutes to 10 hours, and even more preferably 30 minutes to 5 hours.

[0085] The step (β3) and the step (γ3) may be carried out in separate apparatuses, or may be carried out in the same apparatus as long as the temperature can be adjusted to the desired level. When steps (β3) and (γ3) are performed in separate devices, after step (β3), the tertiary molded body is cooled to a temperature at which it can be removed from an apparatus such as an incubator, and then moved to another apparatus such as an incubator or a carbonization furnace to perform step (γ3). When steps (β3) and (γ3) are carried out in the same equipment, an incubator or other such equipment is set to a desired temperature, and the carbon molding (I) impregnated with the thermosetting resin is heat-treated to form a tertiary molding (step (β3)), and then the temperature of the same equipment is raised to the desired temperature and the tertiary molding is further heat-treated to obtain a carbon molding (II) (step (γ3)).

[0086] In addition, when steps (α3) to (γ3) are regarded as one cycle, two or more cycles may be performed, i.e., after step (γ3), steps (α3), (β3) and (γ3) may be repeated one or more times. Furthermore, if necessary, after the step (γ3), the carbon molded body (II) may be graphitized.

[0087] The method for producing a carbon molded body of this embodiment may further include a step (α1) and a step (β1) between the step (c) and the step (d), or may further include a step (α2) between the step (b) and the step (c). The step (α1) and the step (β1) are the same as those in the second embodiment. The step (α2) is the same as those in the third embodiment.

[0088] [Method of manufacturing activated carbon compacts] The method for producing an activated carbon molding of this embodiment is a method for obtaining an activated carbon molding by obtaining a carbon molding (i.e., the carbon molding (I) or the carbon molding (II)) by the above-mentioned method for producing a carbon molding of the present invention, and activating the obtained carbon molding. By activating the carbon molded body obtained by the method for producing a carbon molded body of the present invention, activated carbon having a three-dimensional shape can be easily produced. The carbon molded body to be activated may be graphitized.

[0089] For activation of the carbon molded body, a conventionally known activation method such as a gas activation method or a chemical activation method can be used. In the gas activation method, the carbon molded body is activated by contacting the carbon molded body with an activation gas. The activation gas may be water vapor, air, carbon monoxide, carbon dioxide, hydrogen chloride, oxygen, or a mixture of these.

[0090] In the chemical activation method, the carbon molded body is activated by contacting it with an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide; an alkaline earth metal hydroxide such as calcium hydroxide; an inorganic acid such as boric acid, phosphoric acid, sulfuric acid, or hydrochloric acid; or an inorganic salt such as zinc chloride. In the case of the chemical activation method, after activation, the product or the chemical used may be neutralized with an acid or alkali, or may be removed by washing with water or the like.

[0091] Among the above activation methods, the gas activation method is preferred from the viewpoints of simplicity of the equipment and of not requiring any special treatment after activation, and the gas activation method using water vapor is particularly preferred. The activation can be carried out using a multi-stage furnace, a rotary kiln furnace, a fluidized bed furnace, or the like. EXAMPLES

[0092] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. The materials used in each example are shown below. Various measurement methods are also shown below. The following Examples 3 to 10 and 12 to 18 are working examples, and Examples 1, 2, and 11 are comparative examples.

[0093] [Materials used] As the phenolic resin, a novolac type phenolic resin (manufactured by Gun-ei Chemical Industry Co., Ltd., product name "Resitop PS-1299", mass average molecular weight 13570) was used. As the curing agent, hexaethylenetetramine (manufactured by Mitsubishi Gas Chemical Company, Inc.) was used. Benzoic acid (manufactured by EMERALD KALAMA CHEMICAL) and resorcinol (manufactured by Sumitomo Chemical Co., Ltd.) were used as curing accelerators. As the spherical aggregate, spherical carbon (manufactured by Gun-ei Chemical Industry Co., Ltd., product name "GC-050", sphericity 0.95, average particle size 50 μm) was used. As another binder, polyamide 12 (manufactured by EOS, trade name "PA2200") was used. The mass average molecular weight of the novolac phenolic resin was measured using a GPC measuring device (HLC8320GPC, manufactured by Tosoh Corporation) and a column (TSKgel G3000HXL+G2000HXL+G2000HXL, manufactured by Tosoh Corporation) with polystyrene as a standard substance.

[0094] The compounds shown below were used as the thermosetting resin (impregnating resin). Phenolic resin (PL-2211): A resol-type phenolic resin that is liquid at 25°C (manufactured by Gun-ei Chemical Industry Co., Ltd., product name "Resitop PL-2211", resin content 60% by mass, viscosity 200 mPa s). Phenolic resin (PL-3261): A resol-type phenolic resin that is liquid at 25°C (manufactured by Gun-ei Chemical Industry Co., Ltd., product name "Resitop PL-3261", resin content 60% by mass, viscosity 35 mPa s). Phenolic resin (PL-5614): A resol-type phenolic resin that is liquid at 25°C (manufactured by Gun-ei Chemical Industry Co., Ltd., product name "Resitop PL-5614", resin content 35% by mass, viscosity 10 mPa s). Epoxy resin: A mixture of 88.2 parts by mass of phenol novolac type epoxy resin that is liquid at 25°C (manufactured by Mitsubishi Chemical Corporation, grade "152", resin content 100% by mass, viscosity 1600 mPa s), 1.8 parts by mass of an imidazole-based epoxy resin hardener (manufactured by Shikoku Chemical Industry Co., Ltd., product name "Curesol 2PZ-PW"), and 10 parts by mass of acetone (general reagent), resulting in a resin solution (I) with a resin content of 88.2% by mass and a viscosity of 500 mPa s. Furan resin: A resin solution (II) which is a mixture of 90 parts by mass of furfuryl alcohol, 4 parts by mass of citric acid (general reagent), and 6 parts by mass of ion-exchanged water, has a resin content of 90% by mass, and a viscosity of 10 mPa s.

[0095] [Measurement method] <Measurement of bending strength> The bending strength of each molded article was measured by a method in accordance with JIS K 7171:2022.

[0096] <Density measurement> The volume of each molded product was measured with a caliper, and the weight was then measured using a precision balance, and the "density" was calculated as: test piece weight (g) / test piece volume (cm 3 ) The density of each compact was determined.

[0097] [Example 3] <Preparation of raw material mixture> 5 parts by mass of novolac phenolic resin, 0.8 parts by mass of hexaethylenetetramine, 0.1 parts by mass of benzoic acid, and 0.1 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The entire amount (6.0 parts by mass) of the molding resin composition and 95 parts by mass of the spherical carbon were mixed for 5 minutes in a screw type mixer to obtain a raw material mixture.

[0098] <Production of carbon compacts> A carbon molded body was manufactured by selective laser sintering using a powder layer molding machine (manufactured by Aspect Corporation, product name "RaFaElII HT300") as follows. First, three-dimensional data of the cross-sectional shape of the target carbon molded body at a constant interval was prepared in advance. Using a powder additive manufacturing machine, a 100 μm-thick thin layer made of the raw material mixture was laminated on the bottom surface of the molding chamber installed in the powder additive manufacturing machine. A desired area of ​​this thin layer was irradiated with a CO2 laser under the conditions of laser intensity 40 W, laser scanning speed 10 m / sec, laser diameter 0.32 mm, and laser scanning interval 0.12 mm, and the thin layer was sintered by heating to form a sintered thin layer (step (a)). Next, the bottom of the molding chamber (the molding table) was lowered by one layer, another thin layer of the raw material mixture was laminated on the sintered thin layer, and the desired area of ​​this thin layer was scanned and irradiated with a CO2 laser under the same conditions as before. These lamination and irradiation operations were repeated until the desired carbon molded body was formed, and a rectangular parallelepiped primary molded body 10 mm long, 80 mm wide, and 4 mm high was obtained (step (b)). Next, the raw material mixture in the non-irradiated area of ​​the thin layer was removed, and the primary molded body was taken out. The same process was carried out to prepare three primary molded bodies in total.

[0099] The three primary molded bodies were placed in a test incubator (manufactured by Yamato Scientific Co., Ltd., product name "constant temperature incubator with blower") and heat-treated at 170°C for 60 minutes, thereby further curing the molding resin composition contained in the primary molded bodies to obtain a secondary molded body (I) (step (c)). The resulting secondary molded body (I) was cooled to room temperature (25° C.), and then the bending strength and density of one secondary molded body (I) were measured. The results are shown in Table 1 and FIG.

[0100] Next, the remaining two secondary molded bodies (I) were impregnated with resol-type phenolic resin (PL-2211) as an impregnating resin for 30 minutes (step (α1)), and then placed in a test incubator and heat-treated at 170°C for 60 minutes to further harden the resol-type phenolic resin (PL-2211) impregnated in the secondary molded body (I) to obtain a secondary molded body (II) (step (β1)). The amount of impregnated resol-type phenolic resin (PL-2211) was 28 parts by mass in pure content relative to 100 parts by mass of the secondary molded body (I). The resulting secondary molded body (II) was cooled to room temperature (25° C.), and then the bending strength and density of one secondary molded body (II) were measured. The results are shown in Table 1 and FIG.

[0101] Next, the remaining secondary molded body (II) was placed in a test carbonization furnace and carbonized at 800°C for 60 minutes in a nitrogen stream to carbonize the organic components contained in the secondary molded body (II) and obtain a carbon molded body (X) (step (d)). The resulting carbon molded body (X) was cooled to room temperature (25° C.), and then the bending strength and density were measured. The results are shown in Table 1 and FIG.

[0102] [Example 1] 3 parts by mass of novolac phenolic resin, 0.48 parts by mass of hexaethylenetetramine, 0.06 parts by mass of benzoic acid, and 0.06 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The entire amount (3.60 parts by mass) of the molding resin composition and 97 parts by mass of the spherical carbon were mixed for 5 minutes in a screw type mixer to obtain a raw material mixture. A secondary molded body (I) was produced in the same manner as in Example 3, except that the obtained raw material mixture was used. An attempt was made to impregnate the obtained secondary molded body (I) with a resol-type phenolic resin (PL-2211). However, since the secondary molded body (I) was insufficient in strength, steps (α1), (β1) and (d) could not be carried out, and it was therefore not possible to produce a secondary molded body (II) and a carbon molded body (X). The bending strength and density of the secondary molded body (I) were measured, and the results are shown in Table 1 and FIG.

[0103] [Example 2] A raw material mixture was prepared as in Example 1. A carbon molding (Y) was produced in the same manner as in Example 3, except that the secondary molding (I) was not impregnated with the resol-type phenolic resin (PL-2211), i.e., steps (α1) and (β1) were not performed. The bending strength and density of the carbon molded body (Y) were measured, and the results are shown in Table 2 and FIG.

[0104] [Example 4] 10 parts by mass of novolac phenolic resin, 1.6 parts by mass of hexaethylenetetramine, 0.2 parts by mass of benzoic acid, and 0.2 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The entire amount (12.0 parts by mass) of the molding resin composition and 90 parts by mass of the spherical carbon were mixed for 5 minutes in a screw type mixer to obtain a raw material mixture. Except for using the obtained raw material mixture, a carbon molded body (X) was produced in the same manner as in Example 3. The impregnated amount of the resol type phenolic resin (PL-2211) was 33 parts by mass in terms of pure content per 100 parts by mass of the secondary molded body (I). The bending strength and density of the secondary molded body (I), the secondary molded body (II) and the carbon molded body (X) were measured. The results are shown in Table 1 and FIGS.

[0105] [Example 5] A raw material mixture was prepared in the same manner as in Example 4. The obtained raw material mixture was used to produce a carbon molding (Y) in the same manner as in Example 3, except that the secondary molding (I) was not impregnated with the resol-type phenolic resin (PL-2211), i.e., steps (α1) and (β1) were not performed. The bending strength and density of the carbon molded body (Y) were measured, and the results are shown in Table 2 and FIG.

[0106] [Example 6] 20 parts by mass of novolac phenolic resin, 3.2 parts by mass of hexaethylenetetramine, 0.4 parts by mass of benzoic acid, and 0.4 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The entire amount (24.0 parts by mass) of the molding resin composition and 80 parts by mass of the spherical carbon were mixed for 5 minutes in a screw type mixer to obtain a raw material mixture. Except for using the obtained raw material mixture, a carbon molded body (X) was produced in the same manner as in Example 3. The impregnated amount of the resol type phenolic resin (PL-2211) was 21 parts by mass in terms of pure content per 100 parts by mass of the secondary molded body (I). The bending strength and density of the secondary molded body (I), the secondary molded body (II) and the carbon molded body (X) were measured. The results are shown in Table 1 and FIGS.

[0107] [Example 7] A raw material mixture was prepared in the same manner as in Example 6. The obtained raw material mixture was used to produce a carbon molding (Y) in the same manner as in Example 3, except that the secondary molding (I) was not impregnated with the resol-type phenolic resin (PL-2211), i.e., steps (α1) and (β1) were not performed. The bending strength and density of the carbon molded body (Y) were measured, and the results are shown in Table 2 and FIG.

[0108] [Example 8] A carbon molded body (X) was produced in the same manner as in Example 6. The obtained carbon molded body was placed in a horizontal tubular furnace and heated to 900°C at a heating rate of 5°C / min while flowing nitrogen gas. Next, nitrogen gas that had been passed through hot water previously adjusted to 80°C was introduced, and activation was continued by continuing heating at 900°C for 1 hour while introducing water vapor into the tubular furnace at 4.125 mL / min together with the nitrogen gas. Next, the molded body was cooled while only nitrogen gas was introduced, to obtain an activated carbon molded body. The density of the activated carbon compact was measured, and the results are shown in Table 1.

[0109] [Example 9] 40 parts by mass of novolac phenolic resin, 6.4 parts by mass of hexaethylenetetramine, 0.8 parts by mass of benzoic acid, and 0.8 parts by mass of resorcinol were pulverized in a pulverizer (manufactured by Hosokawa Micron Corporation, product name "ACM") to obtain a powdered molding resin composition. The entire amount (48.0 parts by mass) of the molding resin composition and 60 parts by mass of the spherical carbon were mixed for 5 minutes in a screw type mixer to obtain a raw material mixture. Except for using the obtained raw material mixture, a carbon molded body (X) was produced in the same manner as in Example 3. The impregnated amount of the resol type phenolic resin (PL-2211) was 6.4 parts by mass in terms of pure content per 100 parts by mass of the secondary molded body (I). The bending strength and density of the secondary molded body (I), the secondary molded body (II) and the carbon molded body (X) were measured. The results are shown in Table 1 and FIGS.

[0110] [Example 10] A raw material mixture was prepared in the same manner as in Example 9. The obtained raw material mixture was used to produce a carbon molding (Y) in the same manner as in Example 3, except that the secondary molding (I) was not impregnated with the resol-type phenolic resin (PL-2211), i.e., steps (α1) and (β1) were not performed. The bending strength and density of the carbon molded body (Y) were measured, and the results are shown in Table 2 and FIG.

[0111] [Example 11] 30 parts by mass of polyamide 12 and 70 parts by mass of spherical carbon were mixed for 5 minutes in a screw type mixer to obtain a raw material mixture. A primary molded article was produced in the same manner as in Example 3, except that the obtained raw material mixture was used. The obtained primary molding was placed in a test carbonization furnace and carbonized in a nitrogen stream at 800°C for 60 minutes, but the primary molding did not retain its rectangular shape after carbonization, and no carbon molding was obtained.

[0112] [Table 1]

[0113] [Table 2]

[0114] As is clear from Tables 1 and 2 and FIGS. 1 to 4, it was shown that according to the present invention, carbon molded bodies and activated carbon molded bodies having high strength can be produced. In the case of Example 1, it was not possible to produce the secondary molded body (II) and the carbon molded body. In the case of Example 2, a carbon molded body could be produced, but the strength of the carbon molded body was insufficient and the bending strength of the carbon molded body could not be measured. In the case of Example 11, it was not possible to produce a carbon molded body.

[0115] [Example 12] A raw material mixture was prepared in the same manner as in Example 6. Using the obtained raw material mixture, a carbon molded body (Z1) was produced in the same manner as in Example 3, except that the impregnation time of the impregnation resin in step (α1) was changed to 1 minute. The impregnation amount of the resol type phenolic resin (PL-2211) was 18.8 parts by mass in terms of pure content per 100 parts by mass of the secondary molded body (I). The bending strength and density of the carbon molded body (Z1) were measured, and the results are shown in Table 3.

[0116] [Example 13] A raw material mixture was prepared in the same manner as in Example 6. Using the obtained raw material mixture, a carbon molded body (Z1) was produced in the same manner as in Example 3, except that the impregnating resin in step (α1) was changed to a resol-type phenolic resin (PL-3261) and the impregnation time of the impregnating resin was changed to 1 minute. The impregnated amount of the resol-type phenolic resin (PL-3261) was 19.7 parts by mass in terms of pure content per 100 parts by mass of the secondary molded body (I). The bending strength and density of the carbon molded body (Z1) were measured. The results are shown in Tables 3 and 4.

[0117] [Example 14] A raw material mixture was prepared in the same manner as in Example 6. Using the obtained raw material mixture, a carbon molding (Z1) was produced in the same manner as in Example 3, except that the impregnation resin in step (α1) was changed to a resol-type phenolic resin (PL-5614) and the impregnation time of the impregnation resin was changed to 1 minute. The impregnation amount of the resol-type phenolic resin (PL-5614) was 11.8 parts by mass in terms of pure content per 100 parts by mass of the secondary molding (I). The bending strength and density of the carbon molded body (Z1) were measured, and the results are shown in Table 3.

[0118] [Example 15] A raw material mixture was prepared in the same manner as in Example 6. Using the obtained raw material mixture, a carbon molded body (Z1) was produced in the same manner as in Example 3, except that the impregnating resin in step (α1) was changed to an epoxy resin (resin solution (I)) and the impregnation time of the impregnating resin was changed to 1 minute. The impregnated amount of the resin solution (I) was 34.6 parts by mass in terms of pure content per 100 parts by mass of the secondary molded body (I). The bending strength and density of the carbon molded body (Z1) were measured, and the results are shown in Table 3.

[0119] [Example 16] A raw material mixture was prepared in the same manner as in Example 6. Using the obtained raw material mixture, a carbon molding (Z1) was produced in the same manner as in Example 3, except that the impregnation resin in step (α1) was changed to a furan resin (resin solution (II)) and the impregnation time of the impregnation resin was changed to 1 minute. The impregnation amount of the resin solution (II) was 8.3 parts by mass in terms of pure content per 100 parts by mass of the secondary molding (I). The bending strength and density of the carbon molded body (Z1) were measured, and the results are shown in Table 3.

[0120] [Table 3]

[0121] As is clear from Table 3, it has been shown that the present invention can produce a carbon molded article having high strength even when the impregnation time and type of the impregnation resin are changed.

[0122] [Example 17] A carbon molded body (Z1) was produced in the same manner as in Example 13. The carbon molding (Z1) thus obtained was impregnated with resol-type phenolic resin (PL-3261) as an impregnating resin for 1 minute (step (α3)), and then placed in a test incubator and heat-treated at 170°C for 60 minutes to further harden the resol-type phenolic resin (PL-3261) impregnated in the carbon molding (Z1) to obtain a tertiary molding (step (β3)). The amount of the resol-type phenolic resin (PL-3261) impregnated was 18.3 parts by mass in terms of pure content per 100 parts by mass of the carbon molding (Z1). The obtained tertiary molded body was placed in a test carbonization furnace and carbonized in a nitrogen stream at 800°C for 60 minutes to carbonize the organic components contained in the tertiary molded body, thereby obtaining a carbon molded body (Z2) (step (γ3)). The obtained carbon molded body (Z2) was cooled to room temperature (25° C.), and then the bending strength and density were measured. The results are shown in Table 4.

[0123] [Example 18] A carbon molded body (Z2) was produced in the same manner as in Example 17, except that two cycles were performed, with the steps (α3) to (γ3) constituting one cycle. That is, first, a carbon molded body (Z1) was produced in the same manner as in Example 13. The carbon molding (Z1) thus obtained was impregnated with resol-type phenolic resin (PL-3261) as an impregnating resin for 1 minute (step (α3)), and then placed in a test incubator and heat-treated at 170°C for 60 minutes to further harden the resol-type phenolic resin (PL-3261) impregnated in the carbon molding (Z1) to obtain a tertiary molding (step (β3)). The amount of the resol-type phenolic resin (PL-3261) impregnated was 18.3 parts by mass in terms of pure content per 100 parts by mass of the carbon molding (Z1). The obtained tertiary molded body was placed in a test carbonization furnace and carbonized in a nitrogen stream at 800°C for 60 minutes to carbonize the organic components contained in the tertiary molded body, thereby obtaining a carbon molded body (Z2) (step (γ3)). Next, the obtained carbon molded body (Z2) was cooled to room temperature (25°C), and the steps (α3), (β3) and (γ3) were carried out again in sequence. Note that the impregnation amount of the resol type phenolic resin (PL-3261) in the second step (α3) was 9.3 parts by mass in terms of pure content per 100 parts by mass of the carbon molded body (Z2) obtained in the first step (γ3). The obtained carbon molded body (Z2) was cooled to room temperature (25° C.), and then the bending strength and density were measured. The results are shown in Table 4.

[0124] [Table 4]

[0125] As is clear from Table 4, it was shown that the strength and density of the carbon molded body were increased by increasing the number of times of step (α) and step (β).

Claims

1. A method for producing a carbon molded body, comprising the steps of: A step (a) of forming a thin layer of a raw material mixture containing a molding resin composition and a spherical aggregate, irradiating a desired region of the thin layer with a laser, and sintering the thin layer to form a sintered thin layer; A step (b) of performing the step (a) a plurality of times to obtain a primary molded body in which a plurality of the sintered thin layers are laminated; A step (c) of curing the molding resin composition contained in the primary molded body to obtain a secondary molded body; A step (d) of carbonizing an organic component contained in the secondary molded body to obtain a carbon molded body; Including, The molding resin composition contains a phenolic resin and a curing agent, A method for producing a carbon molded body, wherein a ratio of the phenol resin is 5 parts by mass or more when a total of the phenol resin and the spherical aggregate is 100 parts by mass.

2. The method for producing a carbon molded article according to claim 1 , wherein the spherical aggregate comprises spherical carbon.

3. 2. The method for producing a carbon molded article according to claim 1, wherein a ratio of the phenolic resin is 5 to 50 parts by mass when a total of the phenolic resin and the spherical aggregate is 100 parts by mass.

4. 2. The method for producing a carbon molded body according to claim 1, further comprising: a step (α) of impregnating one or more selected from the primary molded body, the secondary molded body, and the carbon molded body with a thermosetting resin; and a step (β) of curing the impregnated thermosetting resin.

5. A method for producing an activated carbon molded body, comprising obtaining a carbon molded body by the method for producing a carbon molded body according to any one of claims 1 to 4, and activating the obtained carbon molded body.

Citation Information

Patent Citations

  • Method for manufacturing carbon products by three-dimensional printing

    JP2017535445A

  • Method for manufacturing densified carbon products by 3D printing

    JP2018502811A